5x-x-6=6

Simple and best practice solution for 5x-x-6=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-x-6=6 equation:


Simplifying
5x + -1x + -6 = 6

Reorder the terms:
-6 + 5x + -1x = 6

Combine like terms: 5x + -1x = 4x
-6 + 4x = 6

Solving
-6 + 4x = 6

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 4x = 6 + 6

Combine like terms: -6 + 6 = 0
0 + 4x = 6 + 6
4x = 6 + 6

Combine like terms: 6 + 6 = 12
4x = 12

Divide each side by '4'.
x = 3

Simplifying
x = 3

See similar equations:

| log(x/4)(17x-4)=2 | | (-8)+1+(-5)-(-3)= | | x^4+14x+45=0 | | -18=-2x-8 | | 13/20-6/35 | | 5=7x+1 | | 810*(26/45)*x/810 | | 4x^2+77=-36x | | y=x^2+28x+196 | | x-(-87)=56 | | (2x+71)=90 | | 3x-5=2+14 | | (x-4)+72=90 | | 4x^2+29=-28x | | 2x-1=7x+3 | | (2x+17)=90 | | 5y-12-y=0 | | -39-7n=-5+2(-8n-8) | | x-(-14)=-39 | | (x-5)+29=90 | | (8a^-9)^2/3 | | 12=1.5timesp | | -2(t-4)-5= | | (2x+5y)+(x+y)=4+1 | | x^3-9x^2+24x-15=0 | | pq+5q+2p+10= | | x-(-53)=30 | | -3(17q)= | | 912*13/81 | | (x+7)+43=90 | | x^2+20=-12 | | -14x-20=12x+7 |

Equations solver categories